Gambaran Kualitas Hidup Pasien Pasca Mengalami Cedera Kepala: Literature Review - Nanda Agustia; Gamya Tri Utami; Fathra Annis Nauli (Poltekkes Kemenkes Jakarta III, 2021)
Head injury is a type of trauma that is commonly found in emergency departements, this is evidence by the large number of deaths resulting from the incidence of head injuries. if the patient survives and they will have physiological or anatomical disorders that affect to the quality of life. The purpose of this literature study is to find out the quality of life of patients after suffering a head injury. The method used is a literature study obtained from scientific reseach article that searches in accordance with the inclusion criteria, start from 2015 up to 2019 using Google Scholar,Science Direct, and Pubmed. The keyword used are Quality of life, Head Injury. Based on 7 research articles, it was found that 6 out 7 articles stated that there was a decrease in quality of life in post-injury patients with duration of 3, 6, and 12 months, evaluation quality of life the domain of assessment of quality of life that experienced the most decrease was in the physical, psychological, social and cognitive domains, 1 research article stated that there was increase in quality of life after head injury. Based on result there was a decrease in quality of life in post-injury patients